Housing Security of Seniors in Poland – Living Conditions, Financial Burdens, and Housing Satisfaction - Murawska, Anna; Guzowska, Adrianna (Ekonomia i Prawo. Economics and Law, 2025)
Motivation: For every single person, a place of residence is a part of their everyday life and a guarantee of their sense of security. Housing conditions have a significant influence on the overall quality of life. The sense of housing security is crucial, in particular for the elderly. The issue seems to be particularly relevant given demographic aging, as well as the demographic trends that shape both the current and future housing resources for seniors. Aim: The aim of this article is to evaluate the housing security of seniors aged 65 and over in Poland compared to the European Union, with particular emphasis on living conditions, financial burden and housing satisfaction. Method: 9 variables and 27 objects/EU(27) countries were used for assessment. The study covered the years 2013 and 2023, and the data was taken from Eurostat databases. The analysis was based on descriptive statistics, and gaps were calculated taking into account places of residence and age groups. Results: Housing conditions for seniors in Poland are improving, yet structural problems remain serious. Seniors in Poland continue to incur high housing expenses, and this applies most to those living alone. The high satisfaction level of seniors may conceal real difficulties and does not necessarily reflect issues such as poor technical condition of premises, rising maintenance costs, and the lack of housing adapted to the needs of an aging population.